The role of Co–Mo–S type structures in hydrotreating catalysts - Topsøe, Henrik (Applied catalysis. A, General, 2007)
The Co–Mo–S model is used widely to understand and control the catalytic properties of hydrotreating catalysts. Depending on the nature of the support interactions, the Co–Mo–S structures may be present as either Type I or II which has different catalytic properties. Most current high activity industrial hydrotreating catalysts are based on Type II structures. From a fundamental point of view, it has for many years been difficult to understand in detail the catalytic properties of the different types of Co–Mo–S structures since direct atom-resolved insight has not been available. Recently, such insight has been provided by scanning tunneling microscopy (STM) and from the application of density functional theory (DFT) and together with other advances, this has contributed greatly to improve our fundamental knowledge of MoS 2 and Co–Mo–S structures. Many surprising features were discovered. For example, it has been observed that key catalytic steps may involve active sites which are not sulfur vacancies. Of particular interest, it was found that fully sulfur-coordinated sites with metallic-like properties play a role in hydrogenation reactions of such catalysts. The new insight has played a role in the recent introduction of the BRIM™ family of improved industrial hydrotreating catalysts.